An anatomical study of the subarachnoid space surrounding the trigeminal ganglion in horses—in preparation for a controlled glycerol rhizotomy in equids - Becker, Richard; Haenssgen, Kati; Precht, Christina; Khoma, Oleksiy-Zakhar; Hlushchuk, Ruslan; Koch, Christoph; Kaessmeyer, Sabine; de Preux, Mathieu (Frontiers in Veterinary Science, 2024)
Introduction: Equine trigeminal-mediated headshaking is a painful neuropathic disorder comparable to trigeminal neuralgia in humans. The selective destruction of pain fibers within the trigeminal ganglion, called rhizotomy, is the surgical treatment of choice for idiopathic trigeminal neuralgia refractory to medical treatment in humans. The human trigeminal ganglion is enclosed by a dural recess called the Meckel's or trigeminal cave, in which the ganglion is surrounded by a cerebrospinal fluid (CSF)-filled subarachnoid space. During glycerol rhizotomy, glycerol is percutaneously injected in this CSF-filled space. Until now, information about the anatomy of the dural recess and the subarachnoid space surrounding the trigeminal ganglion is lacking in horses. The aim of this study was to explore if a CSF-filled subarachnoid space around the trigeminal ganglion exists in horses.Material and Methods: Six equine cadaver heads were investigated for CSF accumulation around the ganglion with a 3 Tesla MRI. After anatomical dissection to expose the trigeminal root, a polymer-based radiopaque contrast agent was injected through the porus trigeminus into the subarachnoid space (cisternography). The exact delineation and the volume of the contrast agent accumulation were determined on subsequent micro-computed tomographic scans and segmentation. Finally, the distribution of the contrast agent within the subarachnoid space was examined histologically in three specimens.Results: In all 12 specimens included in this study, the trigeminal ganglion was surrounded by a subarachnoid space forming a trigeminal cistern. The mean volume of the trigeminal cave in this study was 0.31 ml (± SD: 0.11 ml). Distribution of the contrast agent along the peripheral nerves (i.e. ophthalmic, maxillary and/or mandibular nerve) was observed in 7 out of 12 specimens.A subarachnoid space surrounding the trigeminal ganglion exists in the horse and could be targeted for glycerol rhizotomy in horses suffering from trigeminal-mediated headshaking. However, the clinical relevance of contrast agent distribution along the peripheral nerves remains to be assessed.